Musician Figures in History: A Study on Hawi al-Funun wa-Salwat al-Mahzun of Ibn al-Tahhan - TURABİ, AHMET HAKKI (KARABUK UNIV, 2020)
Hawi al-Funun wa-Salwat al-Mahzun was written by Ibn al-Tahhan who was one of the palace musicians in Egypt (Fatimids period) between X-XI centuries. According to the available sources, it is the only known musical work that has survived since the Fatimids period. This work, written by a professional musician, consists of two main articles dealing with the scientific and practical aspects of the music art and has an encyclopedic feature with a hundred and two subject titles. One of the most important features that distinguishes Hawi al-Funun wa-Salwat al-Mahzun among early music sources is that the work sheds light on the music of the Fatimids period, as well as the seven hundred musicians who lived between the Jahiliyya period and the Fatimids period. This study, firstly, gives information about Ibn al-Tahhan and his famous study Hawi al-Funun wa-Salwat al-Mahzun, and secondly, as mentioned by Ibn al-Tahhan, gives information about the famous musicians who lived between the period of jahiliyyah and the Fatimids period.
Keywords: Hawi al-funun wa Salwat al-Mahzun; Ibn al-Tahhan; al-Musiqi; Musicians history; Fatimids music; Music theory; Music; Musicology; History of music